BENTUK DAN STRUKTUR PERMAINAN OGUANG JANA JORONG GUGUAK BARUAH NAGARI PADANG LAWEH KABUPATEN TANAH DATAR (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study examines the form and structure of Oguang Jana performances in Jorong Guguak Baruah, Nagari Padang Laweh, Tanah Datar Regency. Oguang Jana is a traditional Minangkabau percussion art form utilizing metal instruments resembling talempong that serves to accompany wedding celebrations, customary events, and the welcoming of honored guests in Nagari Padang Laweh. The research employs a qualitative approach with a descriptive method, focusing on the Oguang Jana tradition in the area. Data collection involved both primary and secondary sources, with the researcher acting as the primary instrument, supported by writing materials and a mobile phone. Data collection techniques included observation, interviews, documentation, and literature review, while data analysis proceeded through stages of collection, reduction, presentation, and conclusion drawing. The findings indicate that Oguang Jana is recognized as a traditional art form and a cultural identity for the people of Padang Laweh, although the frequency of its performance has declined. Performances involve a group of players sitting cross-legged on a tarpaulin sheet, particularly when accompanying the alek pacu jawi (traditional bull race) festival. The Oguang Jana ensemble consists of four instruments with distinct roles: the Cenang sets the tempo (anak); the Jana produces the fundamental sound (dasar); and the Dauk and Pamongek fill the sonic gaps between the Cenang and Jana, acting as interlocking or melody-enriching instruments (paningkah). Modernization has led to a decline in intergenerational transmission and reduced interest among the younger generation in this traditional art form in Nagari Padang Laweh.